Measuring dream recall frequency with questionnaire scales and diaries: reliability and validity - Schredl, Michael (Dreaming, 2025)
Research has demonstrated that we very likely dream every night in every sleep stage; however, the ability to recall a dream upon awakening shows large interindividual as well as intraindividual differences. Over the years, researchers studied the reliability and validity of different dream recall measures. In this study, 81 persons (59 women, 22 men) with a mean age of 24.44 ± 8.49 years completed four different retrospective measures of dream recall and a dream diary over a 4-week period. The findings indicate that all dream recall measures (retrospective and prospective) showed high intercorrelations. As all retrospective measuring (last night, last week, last 28 days) yielded comparable estimates of dream recall frequency, it can be argued that underestimation due to memory might be rather small. In addition, we found the expected logbook enhancement effect, that is, dream recall increased during the 4-week period keeping the diary. The internal consistency (reliability of measuring interindividual differences in dream recall with diaries) was sufficiently high for a 2-week period and very high for the 4-week interval. Lastly, the frequency of “white dreams” was not related to the retrospectively elicited dream recall frequency and, thus, indicates that participants do not include “white dreaming” in their dream recall frequency estimates. (PsycInfo Database Record (c) 2025 APA, all rights reserved)